Testing Long Soaking of Pepper Seeds Locally Infected with The Fungus Colletotrichum capsici by Trichoderma harzianum (Jurnal Online Pertanian Tropik, 2020)
This research aims to determine the viability of local chili seeds infected with Colletotrihum capsici with different soaking times using Trichoderma harzianum. The design used was a Compltely Randomized Design (CRD) consisting of 5 treatments and 4 replications, namely local chili seeds infected with C. capsici mushrooms soaked with T. harzianum suspension for 2 hours, 4 hours, 5 hours, 8 hours, Control (without soaking with T. harzianum suspension). The parameters observed were the percentage of local chili seed germination, Vigor index (IV) local chili seeds, seedling height. The results that the immersion of local chili seeds infected wit C. capsici fungi affected the seed germination, vigor index and heigh chili seedling. The best soaking time is local chili seeds that are soaked for 8 hours.